Application of PDCA cycle management model in home-based nursing of patients with indwelling gastric tubes (PDCA循环管理模式在留置胃管患者居家护理中的应用) - ZHANG Yue (张悦); ZHANG Jingzhi (张京芝) (中西医结合护理)
Objective To use the Plan-Do-Check-Action(PDCA) cycle management model to reduce the number of nursing adverse events in home-based nursing of patients with indwelling gastric tubes. Methods A total of 14 patients who chose to have indwelling gastric tube at home from January to June of 2021 were enrolled. With the informed consent of the patient and his family, indwelling gastric tube placement was performed at home. The PDCA cycle management model was implemented for the home indwelling gastric tube nursing of patients. The occurrence of indwelling gastric tube-associated nursing adverse events and the nursing quality of nursing staff before and after the implementation of PDCA mode were compared. Results After implementation of the PDCA cycle management model, six indicators were regularly monitored daily: the number of nasal strips that were not measured for deep replacement of gastric tubes, residual volume before nasogastric feeding, gastric tube use for more than 28 days, self-extubation, no oral care and other nursing problems. After observation, the number of gastric tubes-associated nursing problems were significantly reduced, with as significant difference (P＜0. 01). Nursing staff had significant improvements in PDCA skills, team spirit, brain development, communication and coordination, activity confidence, responsibility in the PDCA cycle mode. Conclusion The use of PDCA cycle management mode in the home-based nursing of patients with indwelling gastric tubes can reduce the incidence of nursing adverse events, and effectively improve the nursing quality. (目的 运用PDCA循环管理模式减少留置胃管相关护理问题, 提升患者居家护理安全。方法 选取2021年1月—6月共14例接受居家护理的留置胃管患者为研究对象。在患者及其家属知情同意下, 于家中实施留置胃管。运用PDCA循环管理模式开展居家护理, 对比实施PDCA模式前和实施PDCA模式后留置胃管相关护理问题发生情况与护理人员的护理质量。结果 运用PDCA循环管理模式后, 每日定期观察6项指标: 未测量胃管深度更换鼻贴、鼻饲前未回抽检查残余量、胃管使用超过28 d、自行拔管、无口腔护理和其他护理问题的发生数量。实施PDCA循环管理模式后, 留置胃管相关护理问题较实施前减少, 差异有统计学意义(P＜0. 01), 护理人员PDCA循环工具、团队精神、脑力开发、沟通协调、活动信心, 责任荣誉感方面均较改善前有明显改善。结论 对于居家留置胃管患者, 运用PDCA循环管理模式能够减少留置胃管相关护理问题, 有效提升护理人员的护理质量。)